OBIEKTYWNE KRYTERIA USTALANIA WYSOKOŚCI WYNAGRODZENIA A UKŁADY ZBIOROWE PRACY - Kowalczyk, Aneta (Zeszyty Prawnicze, 2016)
Important aspects of the process of determining pay, from the viewpoint of employees, include not only the pay rate, but also the objectivity of criteria taken into account to calculate it. This is because objective criteria are needed to make an employee’s pay right in consideration of both his job and qualifications. Collective labour agreements play an important role in the process of establishing objective criteria for employees’ pay. While the Polish Labour Code describes the criteria in general terms, collective labour agreements should stipulate them in a more specific manner. On the basis of a review of selected collective agreement systems, the author shows to what extent, from the point of view of these collective agreement systems, the solutions applied provide grounds for the objectivity of criteria applied for the calculation of pay. The article also discusses the criteria which employers should apply to calculate their employees’ pay, since the criteria now in use are not objective enough and employers find them hard to verify.